A Study of Job Satisfaction of Assistant Professor Working in Non-Grant Colleges: A Comparative Study of Job Satisfaction among Assistant Professors in Non-Grant Colleges (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Job satisfaction is defined as the extent to which an employee feels self-motivated, content satisfied with hisher job. Job satisfaction happens when an employee feels he or she is having job stability, career growth and a comfortable work life balance. A study was conducted to know job satisfaction of Assistant Professor working in self –financed B.B.A. College of Pune. A descriptive survey method of research was used to collect the data of job satisfaction among Assistant Professor of self-financed B.B.A. College. The sample for the study consisted of 200 Assistant Professor randomly selected from self-financed B.B.A. College located at urban and rural areas of Pune district of Maharashtra state. The colleges were selected on the basis of convenient sampling whereas simple random technique was followed to select the Assistant Professor. A self -developed Adjustment Scale was used to collect the data. The findings of the study show that majority of Assistant Professor of self-financed B.B.A. College were found under moderate level of job satisfaction. The Assistant Professor of urban self-financed B.B.A. College were found to be better satisfied in comparison to the Assistant Professor working in rural self-financed B.B.A. College. The female Assistant Professor of self-financed B.B.A. College were found to be better satisfied than the male Assistant Professor of self-financed B.B.A. College. The mean score of job satisfaction of male Assistant Professor of self-financed B.B.A. College is less than the mean score of job satisfaction of female Assistant Professor of self-financed B.B.A. College. The male and the female Assistant Professor of self-financed B.B.A. College do not differ significantly in their Job satisfaction scale.